A comparison test of equality of two competing risks (2018)
In this paper, it is tackled the problematic of the risks that are competing to cause the failure from the subject; in particular whether the risks or likelihood of failure associated with each type of failure are equally important or whether a risk is more serious than the other. For this purpose will be made a study of hypothesis tests for equality of cumulative incidence functions of associated with risks. A comparative study of some of the test procedures that have been proposed for this purpose, and thus able to determine the behavior of the different tests in various scenarios to evaluate the performance of the same will be made. Test procedures are included using real data of patients with lymphoma.